A comparative study of the tense and aspect in Standard Khasi and its varieties - Rynjah, Rymphang K. (Nepalese Linguistics, 2019)
In this study, we will undertake a comparative study of the syntax of the Tense and Aspect of Standard Khasi, an Austro-Asiatic language spoken in the state of Meghalaya and its two varieties Trangblang and Mawlong. Trangblang belongs to the War-Jaiñtia dialect of Khasi and is spoken in Trangblang village situated in Amlarem Block in Jaiñtia Hills District. Mawlong, on the other hand, is a War-Khasi dialect of Khasi and is spoken in Mawlong village located in the East Khasi Hills District. The main aim of this study is to compare and contrast the similarity and variation between these varieties when compared with the Standard Khasi using a comparative methodology. This study also aims to present the morphology of Tense and Aspect and to account for the syntactic analyses of Tense and Aspect in these varieties.